To investigate the potential of Moringa oleifera leaf extract and broccoli (Brassica oleracea) leaf extract as Sodium sulphite replacers in preserving minced meat - Nyathi, Michelle Y. (Midlands State University, 2017)
Minced meat is a nutritionally dense and highly perishable food, therefore there is need for preserving it. Most artificial preservatives currently used to prevent food spoilage have been reported to cause various health problems hence the need to use natural preservatives. Moringa oleifera and Brassica oleracea (broccoli) leaf extracts have proved their potential to be used as natural preservatives. The main objective of this research was to determine the antimicrobial efficacy of Moringa oleifera and broccoli leaf extracts as minced meat preservatives. Seven minced meat samples were prepared with different preservative concentrations. The first one had no preservative, the second one was preserved with 0.1% sodium sulphite, the third one was preserved with 1% Moringa oleifera leaf extract, the fourth one was preserved with 2% Moringa oleifera leaf extract, the fifth one was preserved with 1% broccoli leaf extract, the sixth one was preserved with 2% broccoli leaf extract and the seventh one was preserved with 1% Moringa oleifera and 1% broccoli leaf extracts. The minced meat samples were tested periodically (after 1, 12, 24, 48 and 72 hours) for microbial load (Total Bacterial Count, Coliforms, Salmonella, Escherichia coli and Staphylococcus aureus), colour stability and sensory analysis. Escherichia coli and Salmonella were not detected in all samples. The Total Bacteria, Staphylococcus aureus and Coliform counts for the samples varied from 4.3- 5.98 log CFU/gram, 1.32- 3.91 log CFU/gram and 3.4- 5.3 log CFU/gram respectively. The colour a*, L* and b*- values had ranges between 5-14, 53.2- 44.2 and 12- 15 respectively. The differences were compared using Graph pad prism 4 one way ANOVA for significant difference (α 0.05). It was concluded that there was no significant difference in the shelf life of the minced meat preserved with broccoli and Moringa oleifera leaf extracts to the one preserved with sodium sulphite.